2009
DOI: 10.1007/s12550-009-0026-y
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of growth and ochratoxin A biosynthesis in Aspergillus carbonarius by flavonoid and nonflavonoid compounds

Abstract: The effect of naturally occurring phenolic compounds on Aspergillus carbonarius growth and ochratoxin A (OTA) production was studied. Caffeic acid and the flavonoids, rutin and quercetin, were added to Czapek Yeast Extract agar at concentrations ranging between 50 and 500 mg/l. All phenolic compounds had a significant influence on growth rate and lag phase of A. carbonarius at 250 mg/l. The growth was completely inhibited with 500 mg/l. In comparison with the control, a significant decrease in OTA production w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
2
11
0
1
Order By: Relevance
“…Other important phenolic compounds found in our extract were quercetin and caffeic acid; these compounds have been shown to completely inhibit growth and aflatoxin production by both A. flavus and A. parasiticus , and growth and ochratoxin A production by Aspergillus carbonarius , and was found effective against A. flavus , A. niger , F. moniliformae and R . bataticola .…”
Section: Discussionmentioning
confidence: 78%
“…Other important phenolic compounds found in our extract were quercetin and caffeic acid; these compounds have been shown to completely inhibit growth and aflatoxin production by both A. flavus and A. parasiticus , and growth and ochratoxin A production by Aspergillus carbonarius , and was found effective against A. flavus , A. niger , F. moniliformae and R . bataticola .…”
Section: Discussionmentioning
confidence: 78%
“…The antifungal activity of the extract may be also due to the other phytochemical constituents, such as naturally occurring phenolic compounds. In other plants, these compounds have been found important for inhibiting growth and toxin production by toxigenic fungi (Guiraud et al, 1995;Beekrum et al 2003;Bisogno et al, 2007;Palumbo et al 2007;Romero et al, 2009). For instance, the growth of A. carbonarius and OTA production may be inhibited by some phenolic compounds (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the growth of A. carbonarius and OTA production may be inhibited by some phenolic compounds (e.g. caffeic acid, quercetin, and rutin), especially at higher concentrations (Romero et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that subinhibitory doses together with inadequate distribution of preservative, especially at low water activities, could enhance fungal growth [37,38]. This behavior was also observed in population of Aspergillus species with some concentration of propionate mixtures [39], trihydroxybutyrophenone (THB) [23], peppermint and boldus [40], quercetin and caffeic acid [41]. This behavior suggests that the combinations of antioxidants should be assayed at several concentrations, with various strains and environmental conditions to find safe concentrations and prevent undesirable effects.…”
Section: Discussionmentioning
confidence: 97%